BIO-EFFICACY OF CROTON BONPLANDIANUM BAILL.ON SOME WEED AND CROP PLANTS
Allelo - chemicals were extracted from the leaves of Croton bonplandianumBaill.using various solvent systems. The seeds of the test plants i.e. Triticum. aestivumL.,SpinaceaoleraceaL.,Vicia sativa L.and MadicagohispidaGaertn.were treated with different extract fractions i.e. Aqueous leachates (AL), Petroleum ether Fraction (PF) Methanolic Fraction (MF) Chloroform Fraction (MF) WaterFraction (WF)